2022
DOI: 10.3389/fpsyt.2022.975936
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on children's mental health: A systematic review

Abstract: BackgroundThe outbreak of COVID-19 in December 2019 has caused unprecedented disruption to the structure of children's daily lives due to school closures, online learning, strict social distancing measures, limited access to outdoor activities and many other restrictions. Since children are more susceptible to stress than adults and there is a growing concern about the potential debilitating consequences of COVID-19 for children's mental health, the present review aims to provide empirical evidence on the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 87 publications
(158 reference statements)
1
21
0
Order By: Relevance
“…Several reviews and studies have examined the short and long-term effects of the COVID-19 pandemic on the mental health of young people [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Bussières et al [ 52 ] found that mental health problems in children up to 13 years of age increased three times more in European countries than in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews and studies have examined the short and long-term effects of the COVID-19 pandemic on the mental health of young people [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Bussières et al [ 52 ] found that mental health problems in children up to 13 years of age increased three times more in European countries than in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, children’s and parents’ gender and age were considered in our analyses but no other variables such as socioeconomic status (besides the school leaving certificate) or parental educational level – both variables that were shown to be of relevance during distant teaching with children from less-educated families with lower economic status made less progress over time than students in higher SES schools (e.g., Segers et al, 2022). Furthermore, socially disadvantaged children also faced higher risks of worsened mental health (Ng & Ng, 2022).…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 In addition, literature shows that COVID-19 caused different mental behaviors among youngsters by worsening the child’s mental health outcomes which was further reflected by the socioeconomic status of the family. 15 Furthermore, the COVID-19 pandemic had a greater negative impact on parents’ mental health. This is because parents have pre-existing vulnerabilities, must manage their work and family commitments in addition to their jobs and household tasks, and require harmony.…”
Section: Introductionmentioning
confidence: 99%